1979
DOI: 10.1128/jb.139.2.507-514.1979
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of bacteria to mammalian cells: inhibition by tunicamycin and streptovirudin

Abstract: Group B streptococci were labeled either by growing the cells in ['4C]fructose or by using the surface label 4,4'-[3H]diisothiocyano-1,2-diphenylethane-2,2'-disulfonic acid, which reacts with amino groups. A quantitative assay was developed by using these labeled bacteria to study the adherence of streptococci to canine kidney epithelial celLs. The bacteria adhered to kidney celLs that had been infected with influenza A virus, but did not adhere to uninfected cells. The binding of 3Hlabeled group B streptococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…These data correlate well with previous studies by Simonsen et al, who showed that , maturation of VSV was completed by 4.5 to 5.5 I h after the start of infection (34). Similar results cn were observed with influenza virus maturation 0 and the antibiotic tunicamycin (27).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…These data correlate well with previous studies by Simonsen et al, who showed that , maturation of VSV was completed by 4.5 to 5.5 I h after the start of infection (34). Similar results cn were observed with influenza virus maturation 0 and the antibiotic tunicamycin (27).…”
Section: Downloaded Fromsupporting
confidence: 92%
“…Both the co‐sedimentation of R1 with S. suis and of R2 with GBS were mediated by a sialic acid‐dependent interaction because both viruses remained in the supernatant when the respective streptococci were pretreated with neuraminidase (NA; Figure a). The NA pretreatment has been confirmed not to affect the bacteria viability (data not showed), which is consistent with previous reports (Butler, Baker, & Edwards, ; Pan, Schmitt, Sanford, & Elbein, ). A similar result was obtained when the supernatants were analysed by an infectivity assay (Figure b).…”
Section: Resultssupporting
confidence: 91%
“…Isotopically labeled bacteria, group B Streptococcus type Ic and S. aureus (strains 1071 and P116), were used in a quantitative assay of bacterial binding to virus-infected and control MDCK cells. The streptococci were labeled with 4,4-[3H]diisothiocyano-1,2-diphenylethane-2,2'-disulfonic acid ([3H]DIDS) (specific activity, 2.024 x 109 cpm/.umol) as previously described (17). This compound is a surface label which forms covalent bonds with amino groups.…”
Section: Bacterial Adherence Test Details Of the Test Sys-mentioning
confidence: 99%